2021
DOI: 10.2147/ijgm.s295490
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Toward Corona virus Infection Among Pregnant Women Attending Antenatal Care at Public Hospitals in Three Wollega Zones, Ethiopia

Abstract: Background: Pregnancy is an immune-suppressed state which makes pregnant women generally more susceptible to COVID-19 infection and severe illness. Extensive precautions have been recommended to avoid exposure to the virus. Knowledge and attitude toward the disease play an integral role in readiness to accept public health measures. This study aimed to assess the knowledge, attitude and practice towards COVID-19 among pregnant women attending antenatal clinics in three Wollega zones, Ethiopia. Methods: Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
17
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 16 publications
10
17
4
Order By: Relevance
“…On the contrary, the findings from previous studies done in Wollega Zone (43.6%), 42 Debre Tabor (47.6%), 43 Ghana (46.6%), 44 and low-resource African settings (30.3%) 33 which were lower than our finding. The possible discrepancy might be the difference in the study setting, socio-demographic characteristics, and study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, the findings from previous studies done in Wollega Zone (43.6%), 42 Debre Tabor (47.6%), 43 Ghana (46.6%), 44 and low-resource African settings (30.3%) 33 which were lower than our finding. The possible discrepancy might be the difference in the study setting, socio-demographic characteristics, and study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…The study result showed that only 44.8% (95% CI: 41.3, 48.7) of the study participants had good adherence with COVID-19 preventive practice. These results are comparable with studies conducted in Ghana 46.6% [ 32 ], Egypt 42.86% [ 34 ], Wollega zone, Ethiopia 43.6% [ 33 ], and Debre Tabor, Ethiopia 47.6% [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…Study participants whose age ≤24 years were 2.89 times more likely to have good adherence with COVID -19 preventive practice as compared to participants whose age was≥35 years. This finding was supported by a study conducted in Nigeria [ 35 ] and studies in different parts of Ethiopia, Wollega zones, [ 33 ], Gurage zone, [ 31 ]. This might be due to younger women having access to information on COVID-19 (risk, mode of transmission, and way of preventive measures) via social media and mass media.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations